1999
DOI: 10.1038/sj.bjc.6690344
|View full text |Cite
|
Sign up to set email alerts
|

Granulocyte colony-stimulating factor (G-CSF) transiently suppresses mitogen-stimulated T-cell proliferative response

Abstract: Summary Granulocyte colony-stimulation factor (G-CSF) is a cytokine that selectively promotes growth and maturation of neutrophils and may modulate the cytokine response to inflammatory stimuli. The purpose of this study was to examine the effect of G-CSF on ex vivo peripheral blood mononuclear cell (PBMC) functions. Ten patients with breast cancer were included in a clinical trial in which r-metHuG-CSF was administrered daily for 5 days to mobilize peripheral blood stem cells. Ten healthy women were also incl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
25
0

Year Published

2000
2000
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(26 citation statements)
references
References 34 publications
1
25
0
Order By: Relevance
“…[7][8][9][10] After G-CSF stimulation in vivo, human and murine T cells show a reduced cytotoxic activity and proliferative response upon in vitro stimulation. 11,12 Monocytes from G-CSF-mobilized human donors have also been shown to suppress T-cell alloreactivity. 11 This suppresion may occur through an interleukin-10 (IL-10)-dependent mechanism 13 and/or through the inhibition of IL-12 and tumor necrosis factor ␣ (TNF-␣) release.…”
Section: Introductionmentioning
confidence: 99%
“…[7][8][9][10] After G-CSF stimulation in vivo, human and murine T cells show a reduced cytotoxic activity and proliferative response upon in vitro stimulation. 11,12 Monocytes from G-CSF-mobilized human donors have also been shown to suppress T-cell alloreactivity. 11 This suppresion may occur through an interleukin-10 (IL-10)-dependent mechanism 13 and/or through the inhibition of IL-12 and tumor necrosis factor ␣ (TNF-␣) release.…”
Section: Introductionmentioning
confidence: 99%
“…6,7 In vitro human studies have demonstrated that PBSC products have high levels of T cell inhibitory activity. [8][9][10][11][12][13] This effect has been variously attributed to the high levels of IL-10 produced by monocytes, 14 to modulation of monocyte function, 15 and more recently, to a mobilisation-associated increase in certain dendritic cell (DC) subsets. 16,17 DC constitute a system of antigen-presenting cells that play a critical role in regulating immune responses.…”
mentioning
confidence: 99%
“…35 After in vivo administration of G-CSF, human and murine peripheral blood T cells have shown reduced cytotoxic activity and proliferative response upon in vitro stimulation. 36 Monocytes of peripheral blood from G-CSF-mobilized human donors have also been shown to suppress T-cell allo-reactivity. This suppression may occur through an IL-10-dependent mechanism, downregulation of CD28/B7(CD80 and CD86) co-stimulatory molecules signals and/or through the inhibition of IL-12 and TNF-alpha release.…”
Section: Discussionmentioning
confidence: 99%